CT angiographic evaluation of perforators in the lower limb and their reconstructive implication - Visweswar Bhattacharya; Neeraj K. Agrawal; Gurab R. Chaudhary; Srivastava Arvind; Siddharth Bhattacharya (Indian Journal of Plastic Surgery)
Background: The perforator flaps evolved on the knowledge of the vascular tree from the main vascular trunk up to the subdermal plexus. Therefore, we thought that it′s necessary to map the whole vascular arcade by CT angiography. The aim of this study is to evaluate the perforators and the whole vascular tree of the lower limb by peripheral CT angiography with 3D reconstruction and intraoperative evaluation. This study helps in designing flaps of different constituents based on the selected perforators. Materials and Methods: Twenty patients having lower limb defects were selected. CT angiography was done using a non-ionic iodinated contrast media injected through the antecubital vein. The lower limbs were imaged using volume rendering CT scan machine. Three dimensional reconstructions were made. The whole arterial tree, along with the perforators, were mapped. Findings of the audio-Doppler were correlated with the CT angiographic observations. Further these evaluations were confirmed by intraoperative findings. Results: The three dimensional CT angiographic reconstruction with bone and soft tissue provided advanced knowledge of this vascular network. It delineated the main vessel, the perforators, their caliber, distance from fixed bony landmarks and course up to the subdermal plexus. These findings were confirmed during dissection of the proposed flap. The perforators were mainly musculocutaneous in the proximal leg and septocutaneous distally. Conclusions: The vascular details visualized by this technique made advancement over the existing methods namely color Doppler, audio Doppler, two dimensional angiography etc. It improved the understanding of perforator flaps and their successful clinical application.